ANALYSIS OF ENTEROCOCCUS FAECALIS, STAPHYLOCOCCUS AUREUS, AND CANDIDA ALBICANS IN CAST METAL CORES (2017)
All dental treatments should strictly follow aseptic protocols in order to reduce failure, especially when performing endodontic procedures. Despite being a key recommendation in this type of interventions, this statement is generally ignored, as students